Review of zeolite mineralizations from the high-grade metamorphosed Strazek Unit, Moldanubian Zone, Czech Republic - Novak,M.; Toman,J.; Skoda,R.; Sikola,D.; Mazuch,J. (Journal of Geosciences, 2023)
Geological position, mineral assemblages, and compositional evolution of several types of mostly hydrothermal zeolite mineralizations were examined in the easternmost part of the Moldanubian Zone (Strazek Unit), Czech Republic, using EPMA and Raman spectroscopy. The zeolite mineralizations are related to the following geological processes: (A1) late magmatic to (A2, A3) hydrothermal crystallization (pseudomorphs, brittle tectonic fractures) in granitic pegmatites; (B) retrograde stages of the Variscan metamorphism - (B1) Alpine-type hydrothermal veins on ductile to brittle fractures with epidote, prehnite and zeolites, (B2) laumontite and (B3) natrolite veinlets; the latter two on thin brittle fissures; (C) hydrothermal zeolite veins with dominant stilbite-(Ca) + heulandite-(Ca) and sulfides on ductile to brittle fractures, and (D) thin brittle fissure-filling veinlets lined with harmotome ± calcite. The zeolite mineralizations include pollucite (A), analcime (A, B), phillipsite-(Ca) (A), harmotome (A, D), chabazite-(Ca) and chabazite-(K) (A, B), thomsonite-(Ca) (A), natrolite (A, B), laumontite (A, B, C), stilbite-(Ca) (B, C), scolecite (B), and heulandite-(Ca) (B, C). The individual zeolite mineralizations differ significantly in their regional distribution: (B) Alpine-type hydrothermal veins and laumontite and natrolite veinlets are widespread within almost the whole region, whereas zeolites in (A) granitic pegmatites and in (C, D) hydrothermal veins are concentrated along the eastern border of the Strazek Unit, the latter two assemblages restricted to the Rozna-Olsi ore field. Fluids with variable composition and origin facilitated the formation of individual zeolite mineralizations. They evolved from moderate-T (˜400 °C) to low-T (˜50 °C) conditions characterized by the following extra-framework cations ± volatiles with dominant H2O: (A1) - Cs, Ba, Ca, Na ˃ K, (A2) - Ca, K, Ba ˃ Na, (A3) - Ca, Na, Ba (A: T ˜400-50 °C); (B1) - Ca ± B, (B2) - Ca, (B3) - Na, Ca (B: T ˜350-50 °C); (C) - Ca ˃ Na ± S, F (C: T ˜240-50 °C); (D) - Ba, Ca ± CO2 (D: T ˜100-50 °C). Sources of fluids include - residual fluids exsolved from pegmatite melt (A1) and external fluids derived from host rock (A2, A3); fluids related to retrograde stages of the Variscan metamorphism (A3?, B1, B2, B3, C?); likely post-Variscan fluids of various origin (C, D). The zeolite assemblages demonstrate that the PTX conditions suitable for their origin were attained in the late stages of distinctive geological processes. Zeolites may be used as a valuable indicator of alkaline to neutral and low-T to very low-T hydrothermal fluids with high activity of Ca, K, Na and/or Ba, and variable aSiO2 on tectonic fractures and fissures.
Keywords: zeolites; mineral assemblages; chemical composition; Strazek Unit; Moldanubian Zone